Granulomatous cellular signatures in nontuberculous and tuberculous mycobacterial infections - Doratt, Brianna M.; Napier, Ethan G.; Boroujeni, Mahdi Eskandarian; Douglas, Sarah; Davies, Michael H.; Bermudez, Luiz; Spindel, Eliot R.; McCaffrey, Erin F.; Messaoudi, Ilhem (Frontiers in Microbiology, 2026)
Mycobacterium tuberculosis (Mtb) and nontuberculous mycobacteria (NTM) are acid-fast bacilli that trigger granuloma formation, a hallmark immune response aimed at containing infection. While the biology of Mtb granulomas has been widely investigated, far less is known about granulomas caused by NTM infection, despite the increasing prevalence and clinical challenge of NTM cases worldwide. Because granulomas influence infection control, pathology, and treatment response, understanding their cellular organization and signaling is critical to improving therapeutic strategies. Therefore, we characterized granulomas formed following infection of rhesus macaques with Mycobacterium avium subsp. hominissuis (MAH) and compared them to granulomas from cynomolgus macaques infected with Mtb. MAH-associated granulomas were enriched in pro-inflammatory macrophages and, within granulomatous regions, both immune and non-immune cells exhibited pronounced inflammatory transcriptional signatures. By contrast, cells in non-granulomatous tissue displayed signatures associated with regulatory, wound-healing responses. Mtb granulomas were overall more inflammatory than MAH granulomas but showed diminished evidence of adaptive immune activation, cellular survival pathways, and signals supporting granuloma structural integrity. Notably, endothelial cells, fibroblasts, and a subset of macrophages were primary drivers of the signaling differences between Mtb and MAH granulomas. These findings highlight fundamental distinctions in granuloma biology between tuberculosis and nontuberculous infections. The reduced adaptive immune signatures and altered survival signaling seen in Mtb granulomas may underlie its aggressive pathology, while MAH granulomas’ distinct macrophage and stromal cell responses may contribute to the chronic, difficult-to-treat nature of this disease. Recognizing these differences could inform targeted therapies and strategies to better manage both tuberculous and nontuberculous infections.